# Equation with fractions

Solve an equation:

$1−62x−5 =3−4x $

It is an equation with fractions.

$1−62x−5 =3−4x $

It is an equation with fractions.

### Correct answer:

Tips for related online calculators

Need help calculating sum, simplifying, or multiplying fractions? Try our fraction calculator.

Do you have a linear equation or system of equations and looking for its solution? Or do you have a quadratic equation?

Do you have a linear equation or system of equations and looking for its solution? Or do you have a quadratic equation?

#### You need to know the following knowledge to solve this word math problem:

#### Grade of the word problem:

## Related math problems and questions:

- Simple equation 6

Solve the equation with one variable: X/2+X/3+X/4=X+4 - Equations 36561

Solve two equations with one unknown: a) 1/6 * x = 3 b) 4/7 = y / 2 - Simple equation 5

Solve equation with fractions: X × 3/8 = 1/2 - Fraction + eq

Solve following simple equation with fractions: -5/6(8+5b) = 75 + 5/3b - Add to subtracting

Solve a simple equation with fractions: n-1/6=1/2 - Solve 12

Solve the following quadratic equation: 3/2-(2x-1)²=5/4 - Polynomial: 8465

Solve the equation with the polynomial: x / 2 + 1/2 + 3 = x - Eq-frac

Solve the following equation with fractions: h + 1/3 =5/3 - Equation 25

Solve the following simple equation: 3/4(x+5)=1/2(x+9) - Fractions: 32541

Solve the following equation with fractions: (5x + 1) / 3 + (17-x) / 2 = (3x + 1) / 8 + 15 - Eqn

Solve equation with fractions: 2x/3-50=40+x/4 - Interesting 8981

Solve an interesting equation: (1 * x) + (2 * x) + (3 * x) + (4 * x) + (5 * x) + (6 * x) = 100 - Equation 4293

Solve the equation and perform the test: 2 (4x + 3) - 2 = 6 - 5 (1 - x) - Equations: 43501

Solve two equations: 7 * (x + 1) - (3x + 1) = 21/2 a / 3-a + 6/12 = 2a-4 - Equations 18023

Solve a system of equations with four unknowns: 2a + 2b-c + d = 4 4a + 3b-c + 2d = 6 8a + 5b-3c + 4d = 12 3a + 3b-2c + 2d = 6 - Equation

Solve the equation and check the result: 1.4x - 3/2 + x - 9,8 = x + 0,4/3 - 7 + 1,6/6 - Equation 7848

Solve the equation with the unknown a: 3 (2a + 1) = (a-3) • 4-5